Determining residential areas based on bioclimatic conditions in Kahramanmaraş, Türkiye - Doğruluk, Ahmet Doğan; Ekercin, Semih; Varlık, Abdullah (Afyon Kocatepe Üniversitesi)
Bioclimatic comfort refers to the climatic conditions that contribute to individuals’ physiological and psychological wellbeing. Criteria such as temperature, relative humidity and wind speed are pivotal in determining bioclimatic comfort. Bioclimatic areas should be taken into consideration in urban planning studies for both human well-being and energy saving. This study endeavors to identify bioclimatic comfort areas tailored for Kahramanmaraş. 57 years of climate data obtained from 32 meteorological stations were used. These data were imported into ArcGIS 10.8 geographic information systems (GIS) software. Bioclimatic comfort levels were analyzed on a monthly, seasonal, and annual basis, employing the Discomfort Index (DI), Heat Index (HI), and Wind Chill Index (WCI). The findings revealed that the optimal bioclimatic conditions fell within specific ranges: a temperature range of 18-25°C, relative humidity between 32-48%, and a wind speed of 1.25 – 2.75 m/s. Ten classes were generated based on bioclimatic suitability. The areas characterized by almost unsuitable bioclimatic comfort cover are 426 km2 and 2.93%, less suitable areas encompass 9106 km2 and 62.69%, and moderately suitable bioclimatic comfort areas span 4993 km2 and 34.38%.

Biyoklimatik konfor insanlar için hem fizyolojik hem de psikolojik olarak kendilerini sağlıklı hissettikleri iklim koşullarıdır. Biyoklimatik konforun belirlenmesinde sıcaklık, bağıl nem ve rüzgâr hızı gibi kriterler kullanılmaktadır. Hem insan sağlığı hem de enerji tasarrufu için biyoklimatik alanlar şehir planlama çalışmalarında dikkat edilmelidir. Bu çalışmada Kahramanmaraş ili için biyoklimatik konfor alanlarının belirlenmesi amaçlanmıştır. 32 meteoroloji istasyonundan 57 yıllık iklim verileri kullanılmıştır. Bu veriler ArcGIS 10.8 coğrafi bilgi sistemleri (CBS) yazılımına aktarılmıştır. Discomfort Index (DI), Heat Index (HI) ve Wind Chill Index (WCI) kullanılarak biyoklimatik konfor aylık, mevsimlik ve yıllık olarak belirlenmiştir. Bu araştırma ile biyoklimatik koşulların en uygun olduğu zamanlarda sıcaklık 18-25°C, nispi nem %32-48 ve rüzgâr hızı ise 1.25-2.75 m/s olarak hesaplanmıştır. Biyoklimatik açıdan uygunluk durumuna göre on sınıf oluşturulmuştur. Biyoklimatik konforun neredeyse uygun olmadığı alanlar 426 km2 ve %2.93, biyoklimatik konforun az uygun olduğu alanlar 9106 km2 ve %62.69, biyoklimatik konforun orta uygun olduğu alanlar 4993 km2 ve %34.38 oranındadır.
Biyoklimatik koşullara dayalı yerleşim alanlarının belirlenmesi Kahramanmaraş, Türkiye
Keywords: Geographic Information Systems; Bioclimatic Comfort; Discomfort Index; Landscape Planning; Climatic Parameters; Coğrafi Bilgi Sistemleri; Biyoklimatik Konfor; Rahatsızlık İndeksi; Yerleşim Alanı Belirleme; İklim Parametreleri